Effect of heat treatment on mechanical properties of 3D printed PLA. (November 2021) - Jayanth, N.; Jaswanthraj, K.; Sandeep, S.; Mallaya, N. Harish; Siddharth, S. Raghul
Abstract: Polylactic acid (PLA) is one of the predominant filaments used in the process of 3D printing which is a type of Additive Manufacturing (AM) technology in which a printer prints the semi-molten filament on the bed, layer by layer forming a part of the desired dimension. The final 3D printed parts generally have lower mechanical properties than conventional manufacturing techniques such as injection moulding. The primary reasons for the comparatively poor mechanical property are the poor formation of bonds between inter-filaments and the residual thermal stresses induced due to the temperature difference while 3D printing the filament. Heat treatment of the 3D printed part can significantly reduce the internal stresses developed during the process of printing and also improve the formation of bonds between inter-filaments. The mechanical properties of the PLA, particularly tensile properties can be enhanced to about 80% by heat treating to about 100 °C for 4 h. Heat distortion temperature (HDT) test is used to analyze the heat resistance of the specimens. HDT test also showed an improvement of the heat resistance of heat-treated parts compared to the non-heat treated of about 73%. There is a significant improvement in the mechanical properties just by heat-treating the 3D printing parts compared to the parts that were not heat treated.